Peran Orang Tua dalam Meningkatkan Minat Baca Siswa Kelas IV di MIN 8 Aceh Tengah - Putri Wulan Dhari; Cici Sundari; Asnawi Asnawi (Departement of Mathematics Education, 2024)
The study on 'The Role of Parents in Enhancing Reading Interest Among 4th Grade Students at MIN 8 Aceh Tengah' reveals several significant findings. The reading interest of 4th-grade students at MIN 8 Aceh Tengah appears to be limited, with an average percentage of approximately 50%. Factors such as low student interest and the impact of two years of online learning are primary contributors to this reduced reading enthusiasm. On the other hand, the role of parents is considered relatively effective in boosting children's reading interest, with an average percentage of around 85%. Parental efforts in providing motivation, attention, and support in guiding children to read and providing reading materials are crucial factors in this regard. However, obstacles faced by parents in enhancing their children's reading interest include a lack of children's inclination to read, easily getting bored while reading, and preferring to play with friends rather than reading.